WLAN Localization Measurement and Analysis Using RSS and TOA Positioning Methods - Lorvannger, Khounhack; Lakanchanh, Donekeo; Tiengthong, Thanadol; Promwong, Sathaporn (My University, 2018)
Wireless local area network (WLAN) has been exclusively research due to its widely used applications. Its operate frequency spectrum is in the ISM band and regulated in IEEE 802.11 family. Localization is one of the application which able to used WLAN signal. Its can be used in various applications such as logistics, security, disaster rescue operation tracking, and military service. Since the various kind of its applications is work in indoor environment, the indoor localization requires high accuracy. The receive signal strength (RSS) and time of arrival (TOA) are a parameter that used in the comparison between min-max technique and trilateration technique in this paper. In the measurement of this research, the frequency bandwidth is ranging from 2.3 GHz to 2.5 GHz, an access point is used to represent both of transmit antenna and receive antenna. The cumulative distribution function (CDF) is used for study the most accuracy.
Keywords: indoor localization; positioning method; RSS; TOA; WLAN